Rethinking Administrative Law for Algorithmic Decision Making. - Williams, Rebecca (Oxford Journal of Legal Studies)
The increasing prevalence of algorithmic decision making (ADM) by public authorities raises a number of challenges for administrative law in the form of technical decisions about the necessary metrics for evaluating such systems, their opacity, the scalability of errors, their use of correlation as opposed to causation and so on. If administrative law is to provide the necessary guidance to enable optimal use of such systems, there are a number of ways in which it will need to become more nuanced and advanced. However, if it is able to rise to this challenge, administrative law has the potential not only to do useful work itself in controlling ADM, but also to support the work of the Information Commissioner's Office and provide guidance on the interpretation of concepts such as 'meaningful information' and 'proportionality' within the General Data Protection Regulation.